SNS 이용 동기와 사회적 지지가 문화적응에 미치는 영향 - 국내 거주 중국인 유학생의 문화적응을 중심으로 - 문신일(Shin-Il Moon); 료가(Liao Jia); 이현주(Hyunjoo Lee); 김기태(Kitae Kim) (한국콘텐츠학회 논문지, 21(1), 2021)
A recent rapid growth in the number of Chinese international students in Korea has generated interest in the key factors to affect their acculturation in domestic culture. In accordance with the growing interest, the present study aims to empirically test and analyze the effects of demographics (gender, age, the length of stay, the length of Korean language education and the level of Korean language skills), SNS use patterns (personal network sizes and hours of use for Korean and Chinese SNS, and motivations of Korean or Chinese SNS uses), and social support through Korean and Chinese SNS on acculturation for Chinese international students in Korea. A total of 322 Chinese international students in Korea participated in the online survey. Results showed that use of Chinese SNS for entertainment had an negative impact on the acculturation, while the use of Korean SNS had an overall positive impact. Finally, this study suggests that the practitioners regarding the issue of acculturation for international students in Korea should focus more on specific guidelines to help their appropriate SNS uses rather than on to prevent their SNS addiction problems. 최근 국내 중국 유학생 수가 가파르게 증가함에 따라 국내 중국 유학생들의 문화적응에 영향을 주는 요인에 대한 관심 역시 증가하고 있다. 본 연구는 개인적 특성(성별, 연령, 국내 체류 기간, 한국어 교육 기간, 한국어 구사 능력), SNS 이용행태(네트워크 크기, 이용량, 이용목적), 중국인이나 한국인으로부터의 사회적 지지 세 가지 차원을 고려하여 관련 요인들이 국내 중국인 유학생들의 한국 문화적응에 미치는 영향 정도를 위계적 회귀분석을 통해 실증적으로 분석하였다. 총 322명의 국내 거주 중국인 유학생을 대상으로 온라인 설문조사를 실시한 결과, 중국 유학생들이 한국 SNS를 이용해서 한국 친구들로부터 사회적 지지를 얻는 행위는 문화적응에 긍정적 영향을 주지만, SNS상의 중국 친구들과 시간을 보내고 타국살이의 외로움을 달래면서 사회적 지지를 얻는 방식은 한국 문화적응에 도움이 되지 않고 오히려 한국 문화적응에 부적인 효과를 불러일으킬 수 있다는 점을 발견했다. 따라서 본 연구는 교육 및 실무적인 차원에서 SNS 중독과 같은 병리적인 현상에만 관심을 쏟기보다 유학생들이 국내 문화적응에 도움이 되는 방향으로 SNS 이용을 유도하는 것이 유학생들의 문화적응에 더 도움이 되는 방안 및 정책이 될 것이라 제안한다.